Analyzing the affliction Meaning in the Symbol of the Ritual of children’s purify - Erdenechuluun, Gerelmaa (Mongolian Journal of Arts and Culture, 2024)
A ritual is a social model intertwined with human life, practices, and customs, creating a framework for human actions that have shaped cultural heritage through ancient rituals. These rituals have been a central focus of research across various social sciences and humanities, including cultural studies, psychology, religious studies, ethnology, anthropology, and sociology. Traditional rituals specifically related to children form a significant part of Mongolian customs, passed down through centuries. They embody profound symbolic meanings, such as safeguarding children from potential dangers, illnesses, and hardships while bestowing blessings for health and longevity. This article explores the symbolic aspects of rituals associated with children, with a focus on the ritual of purifying, using ethnographic field research to examine the nature of affliction embedded in these symbolic actions. In ritual studies, concepts like “affliction”, introduced by researcher such as V.Gennep, V.Turner, and C.Bell, involve analyzing actions undertaken in response to fear, suffering, conflict, or struggle. This concept helps deepen our understanding of social and cultural transformations, people’s mentality, and the main characteristics of rituals in a given community Хүүхэд ширгэлэх зан үйлийн бэлгэдэл дэх аффликяцийн утгыг шинжлэх нь Хураангуй: Зан үйл (ritual) нь хүний аж амьдралтай уялдан хэвшиж тогтсон заншил, түүнтэй холбогдох аливаа хүмүүний үйл, нийгмийн загвар бөгөөд эртний олон зан үйл хүн төрөлхтний соёлын өвийг бүрдүүлж байна. Зан үйл нь соёл судлал, сэтгэл судлал, шашин судлал, угсаатны зүй, антропологи, социологи зэрэг нийгэм, хүмүүнлэгийн шинжлэх ухааны судалгааны анхаарлын төвд байсаар ирсэн. Ялангуяа хүүхдэд холбогдох уламжлалт зан үйл нь монгол зан заншлын томоохон хэсэг бөгөөд хүүхдийг аливаа аюул, өвчин зовлонгоос хамгаалах, эрүүл энх, урт удаан наслахыг ерөөсөн гүн утга бэлгэдлийг өөртөө шингээсэн байдаг. Бид энэхүү өгүүлэлд хүүхдэд холбогдох зан үйл тэр дундаа хүүхэд ширгэлэх зан үйлийн бэлгэдлийг угсаатны зүйн хээрийн судалгааны эх хэрэглэгдэхүүнд тулгуурлан судалж, түүний бэлгэдэл дэх аффликяцийн мөн чанарыг судлан тодруулахыг оролдлоо. Зан үйл судлалд В.Женнеп, В.Түрнер, К.Белл зэрэг эрдэмтдийн дэвшүүлсэн аффликяци хэмээх ойлголт буюу хүний оршихуй дахь аливаа айдас, зовлон зүдгүүр, зөрчил, тэмцлийн үед хийж буй үйлдлийн мөн чанарыг шинжлэх нь нийгэм, соёлын өөрчлөлт, ард түмний оюун санаа, зан үйлийн онцлогийг гүн гүнзгий ойлгоход дөхөм болно гэж үзэж байна. Түлхүүр үгс: зан үйл судлал, аффликяци, уламжлал, бэлгэдэл, ширгийн хэрэглэгдэхүүн, лиминал, зан үйлийн мөн чанар